Carotid Reservoir Pressure Decrease After Prolonged Head Down Tilt Bed Rest in Young Healthy Subjects Is Associated With Reduction in Left Ventricular Ejection Time and Diastolic Length - Palombo, Carlo; Kozakova, Michaela; Morizzo, Carmela; Losso, Lorenzo; Pagani, Massimo; Salvi, Paolo; Parker, Kim H.; Hughes, Alun D. (Frontiers in Physiology, 2022)
Background: The arterial pressure waveform reflects the interaction between the heart and the arterial system and carries potentially relevant information about circulatory status. According to a largely the commonly accepted “wave transmission model”, the net BP waveform results from the oversuper-imposition of discrete a forward and a backward pressure wavesdiscrete components, with the first oneforward wave in systole determined mainly by the left ventricular (LV) ejection function and the second backward by the wave reflection from the periphery, the timing and amplitude of which depend on arterial stiffness, and the wave propagation speed and the extent of downstream impedanceadmittance mismatching. However, in this approach aorta is regarded as a rigid tube, and its ignoresobscures the “windkessel function” of the elastic arteriesis neglected. More rRecently, a “reservoir-excess pressure” model has been proposed, based upon the premise that not all changes in aortic pressure can be ascribed to forward and backward traveling waves , and interpreting which interprets the arterial BP waveform as a composite of a volume-related, “reservoir” pressure, and a wave-related (“excess”) pressure. Methods: In this study we applied the reservoir-excess pressure approach to the analysis of carotid arterial pressure waveforms (applanation tonometry) in ten young healthy volunteers before and after a 5-week head-down tilt bed rest which induced a significant reduction in stroke volume (SV), end-diastolic LV volume and LV longitudinal function without significant changes in central blood pressure, cardiac output, total peripheral resistance and aortic stiffness. Forward and backward pressure components were also determined by wave separation analysis. Results: compared to the baseline state, bed rest induced a significant reduction in LV ejection time, diastolic time, backward pressure amplitude, and pressure reservoir integral (INTPR). INTPR correlated directly with LV ejection time, diastolic [not defined yet??], and stroke volume, while excess pressure integral (INTXSP) correlated directly with central pressure. In multivariate analysis INTPR was independently related to LV ejection time and diastolic time, and INTXSP to central systolic BP. Conclusions: This is an hypothesis generating paper which adds confirmation [support??] to the idea that the reservoir-wave hypothesis applied to noninvasively obtained carotid pressure waveforms is of potential clinical usefulness